Biometric key distribution solution with energy distribution information of physiological signals for body sensor network security. Issue 2 (1st June 2013) - Miao, Fen; Bao, Shu‐Di; Li, Ye
Abstract : Recently, a kind of lightweight and resource‐efficient biometrics‐based security solutions were proposed for the emerging body sensor network (BSN). In such security solutions, physiological characteristics that can be captured by individual sensors of BSN were proposed to generate entity identifiers (EIs) for securing keying materials by a biometric approach. In this study, the authors focus on an improved key distribution solution with the energy distribution information of physiological signals (EDPSs) ‐based EIs. Firstly, different EDPS‐based EI generation schemes are studied. Based on the existing multi‐windows Fourier transform scheme, a modified one with single‐window is proposed to improve the identification performance of the generated EIs. Then, a different method based on the discrete cosine transform of the autocorrelation sequence of physiological signals is proposed aiming for a significant increase in identification rates. The performances of time‐varying randomness and identification rates are evaluated to examine EI's feasibility in securing the transmission of keying materials. Based on the characteristics of generated EIs, the corresponding key distribution solution, that is, user‐dependent fuzzy vault, is proposed. A detailed system performance analysis in terms of half total error rate, anti‐attack ability, as well as computational complexity, is conducted to demonstrate the effectiveness of the proposed solution.